2020
DOI: 10.3389/fpsyg.2020.566886
|View full text |Cite
|
Sign up to set email alerts
|

Wearing Face Masks Strongly Confuses Counterparts in Reading Emotions

Abstract: Wearing face masks is one of the essential means to prevent the transmission of certain respiratory diseases such as coronavirus disease 2019 (COVID-19). Although acceptance of such masks is increasing in the Western hemisphere, many people feel that social interaction is affected by wearing a mask. In the present experiment, we tested the impact of face masks on the readability of emotions. The participants (N = 41, calculated by an a priori power test; random sample; healthy persons of different ages, 18-87 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

86
485
18
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 376 publications
(603 citation statements)
references
References 42 publications
(71 reference statements)
86
485
18
14
Order By: Relevance
“…To better understand their collateral psychological consequences, we investigated face masks' effect on emotional and social inferences. Emotion-recognition accuracy declined for masked (vs. unmasked) faces (see also Carbon, 2020). Moreover, we linked lower accuracy to being male (vs. female), being old (vs. young), seeing an old (vs. young) target face, and to seeing a negative (vs. non-negative) emotional expression (e.g., Fölster et al, 2014;Ruffman et al, 2008).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…To better understand their collateral psychological consequences, we investigated face masks' effect on emotional and social inferences. Emotion-recognition accuracy declined for masked (vs. unmasked) faces (see also Carbon, 2020). Moreover, we linked lower accuracy to being male (vs. female), being old (vs. young), seeing an old (vs. young) target face, and to seeing a negative (vs. non-negative) emotional expression (e.g., Fölster et al, 2014;Ruffman et al, 2008).…”
Section: Discussionmentioning
confidence: 85%
“…As face masks reduce facial cues by covering the mouth and part of the nose, they may undermine people's ability to correctly recognize emotional expressions. Indeed, adult participants exhibited lower accuracy rates for faces whose mouth regions was covered (vs. not;Carbon, 2020). Therefore, we expected that wearing a face mask (vs. not) negatively impacts emotion-recognition accuracy (H1).…”
Section: Facial Emotion Recognition and Factors Influencing Itmentioning
confidence: 96%
See 1 more Smart Citation
“…They were presented in an empty room with an angry, happy or neutral facial expression, or with a white face mask. When the virtual character had a face mask, the facial emotion was neutral so as to avoid confounding factors [23]. Both the characters and the empty room were built on Unity (2018.2.21f1 version).…”
Section: Apparatus and Stimulimentioning
confidence: 99%
“…As expected, these results showed that when only the upper part of the face is visible (i.e., the eyes), participants perceive and recognize negative emotions (i.e., anger and fear) better than positive (i.e., happiness) ones. Furthermore, some studies also demonstrated that Islamic contextual cues bias perception toward more intense negative emotions 9,10 . In the last months, many scholars have addressed the social and emotional consequences of COVID-19 on people's well-being [11][12][13] , but very few have considered the social negative consequences of wearing a sanitary face mask [14][15][16] . Indeed, the presence of the sanitary mask may in uence not only the recognition and comprehension of others' emotions, but, given its current status as a contextual cue of the pandemic, also the attribution of physical and social distance.…”
Section: Introductionmentioning
confidence: 99%